PENGARUH PELAKSANAAN PROMOSI TERHADAP MINAT BELI KONSUMEN PADA HOTEL MONA PLAZA PEKANBARU - Firda, Hijratul; Andri, Seno (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Research aim is to find out how about the promotion (advertising, personal selling, sales promotion and public relations) for achieve the room and to find out the consumer’ interest about (interest transactional, referential interest, interest prehensile and exploratory interest).The population of this research is the consumers of Hotel Mona Plaza Pekanbaru. with sampling of 100 people using the formula Slovin. Search procedures performed by accidental sampling of respondents. The research data in the form of primary data, with the questionnaire as a research instrument, data analysis used is by using statistical analysis with SPSS.The result concluded that the result of the respondents responses about promotion in the Mona Plaza Hotel Pekanbaru Based on the results of research by the authors took a conclusion influence of promotion (advertising, personal selling, sales promotion, public relations and immediately marketing) against the consumer interest (transactional interest, referential interest, prehensile interest and exploratory interest) on Mona Plaza Hotel Pekanbaru in the category of agree while the rsults of resondents responses about the interest of consumers in the category of interested expression.through test partial to found the result showed that promotion variable positive influential towards interest consumers buy in the Hotel Mona Plaza Pekanbaru.Keywords: promotion, consumers interest